Effects of olanzapine on serum protein phosphorylation patterns in patients with schizophrenia - Jaros, Julian A.; Rahmoune, Hassan; Wesseling, Hendrik; Leweke, F. Markus; Ozcan, Sureyya; Guest, Paul C.; Bahn, Sabine (Proteomics. Clinical applications, 2015)
Purpose: Previous studies have shown that blood serum phosphoproteins are altered in schizophrenia patients in comparison to controls. However, it is not known whether phosphoproteins are also changed in response to treatment with antipsychotics. Experimental design: Blood samples were taken from patients (n = 23) at baseline and after 6 weeks of olanzapine treatment. Immobilized metal ion affinity chromatography (IMAC) was used for enrichment of serum phosphoproteins and these were analyzed by label-free LC-MS in expression mode (LC-MSE). Results: We identified 11 proteins that were changed significantly in overall abundance and 45 proteins that showed changes in phosphorylation after the antipsychotic treatment. The altered phosphoproteins were mainly involved in the acute phase response, lipid and glucose homeostasis (LXR), retinoic acid signaling (RXR), and complement pathways. Some of the proteins showed a marked increase in phosphorylation, including apolipoprotein A-I (3.4-fold), alpha-1-anti-chymotrypsin (3.1-fold), and apolipoprotein B-100 (2.2-fold). In addition, several proteins showed either decreased phosphorylation (e.g. complement C4A, collagen alpha-1 chain, complement factor H) or a mixture of increased and decreased phoshphorylation (e.g. afamin, complement C5, complement factor B). Finally, 24 of the altered phosphoproteins showed opposite directional changes in a comparison of baseline schizophrenia patients before and after treatment with olanzapine. These included alpha-1B-glycoprotein, apolipoprotein A-IV, vitamin D-binding protein, and prothrombin. Conclusions and clinical relevance: These data demonstrate the potential for future studies of serum phosphoproteins as a readout of physiological function and might have utility in studies aimed at identification of biomarkers for drug response prediction or monitoring.